Risk factors and HIV infection among patients diagnosed with deep vein thrombosis at a regional/tertiary hospital in Kimberley, South Africa - F. K. Mampuya; W. J. Steinberg; J. E. Raubenheimer (South African Family Practice)
Background: Common risk factors for developing deep vein thrombosis (DVT) are prolonged immobilisation, surgery, leg trauma or fracture, pregnancy, hormone therapy, heart failure, cancer, obesity, age, and smoking. The incidence of DVT in HIV-infected patients shows a two- to tenfold increase in comparison with a healthy population of similar age. This retrospective descriptive study evaluated the presence of risk factors for DVT and the prevalence of HIV infection in patients with confirmed DVT treated at Kimberley Hospital Complex, a regional/tertiary hospital in the Northern Cape Province, South Africa, from January 2010 to December 2014. Methods: Patients were identified from the ultrasound register from the Radiology Department, and all adult patients with Doppler-proven DVT during the five-year period were included in the study. The data were extracted from the patient files and captured on data sheets. Results: Of the 852 patients included in the study, most were female (n = 536, 62.9%). The median age was 45 years (range 5–94 years, interquartile range 34–58 years). More than half (n = 443, 52.0%) of the patients were HIV-positive, 333 (39.1%) HIV-negative, while 76 (8.9%) did not have a known HIV status. The most common association with DVT was HIV infection (52.0%) followed by tuberculosis (12.4%), cancer (10.9%), and smoking (9.0%). The least common risk factors were long-distance travel (0.4%) and thrombophilia (0.4%). The left popliteal vein was the most frequently affected site (42.0%) followed by left superficial femoral vein (40.8%) and left common femoral vein (34.7%). The location of the DVT was not associated with the HIV status of the patients. Conclusion: At Kimberley Hospital Complex, the most common risk factor in patients presenting with DVT was HIV infection, with more than half of the patients being HIV-positive. Other risk factors included tuberculosis, cancer and smoking.